2004
DOI: 10.1136/sti.2004.010355
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the sexual behaviour of men who have sex with men and the structure and composition of their social networks

Abstract: Objective: This exploratory study identified associations between the number of sexual partners reported by men who have sex with men (MSM) and the structure and composition of their social networks. Methods: A cross sectional survey was conducted of men recruited as key informants, through advertising and chain referral. A face to face interview was conducted with 206 MSM. The interview included information on the number of sexual partners in the previous year and sociodemographic and behavioural characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 4 publications
(1 reference statement)
8
58
0
Order By: Relevance
“…In relation to the description of networks, friendship network proved to reflect the closest relationships, with more recent contact, unlike the overall network, which showed more distant relationships (acquaintances). The mean number of links dropped from 133 in the sexual partner network to 18 MSM in the friendship network, similar to findings from other studies 34,35,36,37 . Recruiters had a mean of 12 MSM friends, reinforcing the tendency towards very close social relations among individuals in the friendship network.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In relation to the description of networks, friendship network proved to reflect the closest relationships, with more recent contact, unlike the overall network, which showed more distant relationships (acquaintances). The mean number of links dropped from 133 in the sexual partner network to 18 MSM in the friendship network, similar to findings from other studies 34,35,36,37 . Recruiters had a mean of 12 MSM friends, reinforcing the tendency towards very close social relations among individuals in the friendship network.…”
Section: Discussionsupporting
confidence: 80%
“…Studies on sexually transmitted infections have shown that in some networks, a high number of sexual partners is related to large size of the social network of MSM 19,37 , which our study corroborated for both casual and steady partners. Although some correlations were moderate, they were statistically significant, indicating that the more the links among MSM, the more the sexual partners.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Social network characteristics such as network size, composition and density have also been influential in sexually transmitted disease transmission and injection drug use behavior [22][23][24][25]. In a study of sexual behaviors and the composition of social networks among an MSM study group, high risk sexual behaviors were correlated with the number of network members who were HIVpositive, the number of high risk sexual partners and the proportion of people in the network who knew each other (eg network density) [23].…”
Section: Introductionmentioning
confidence: 99%